Barns fysiska aktivitet, sömn och skärmtid i relation till familjens socioekonomiska ställning : en tvärsnittsstudie gjord på finska 3–4-åriga barn och deras föräldrar : SUNRISE Finland pilotstudie - Öhman, Lilja (2023)
Background Previous research suggests that family background has an impact on children's health behaviors such as the amount of physical activity (PA), sleep, and screen time. One factor in family background that is considered to be linked to children's health behavior is the family's socioeconomic status. The aim of the dissertation was to examine whether physical activity, sleep, and screen time vary among 3–4-year-old children depending on their parents' educational level and household income level. Additionally, the aim was to investigate any gender differences and the percentage of children who meet the World Health Organization (WHO) recommendations regarding physical activity, sedentary behavior, sleep, and screen time according to socioeconomic status.